LEADERSHIP STYLE, WORK DISCIPLINE OF LECTURERS IN ISLAMIC HIGHER EDUCATION - Muhammad Agus Kurniawan (IAI AGUS SALIM METRO LAMPUNG, 2022)
To improve the quality of education, it is necessary to have a leadership pattern that empowers all members of the academic community. In other words, it can be said that the leadership model is an important factor in school administration because it refers to a phenomenon of one's ability to move, guide, and direct others in a collaboration. In practice, implementing quality leadership in managing schools often does not materialize. This is caused by a lack of leadership competence (leadership). The main problem faced by universities is the incompetence of leaders in leading universities. The low empowerment of human resources in the academic sphere is basically caused by unsystematic patterns of thinking, organizing, and analyzing education. many positions in universities are given to people who do not have sufficient expertise. Style is the ability to act, strength or attitude, gesture, or variety (way, appearance, form) that is special (regarding writing, essays, language use, building houses). Thus, the leadership style referred to here is an attitude or way of doing that is used in carrying out or carrying out a leadership task